PENINGKATAN LEVEL KEBERDAYAAN PRODUK UNGGULAN KWT SEKAR MAKMUR CEMBING TRIMULYO JETIS BANTUL - Haha Nusa, Gerlan; David Sulistiyantoro; Muhammad Luqman Bukhori; Aris Wahyu Murdiyanto; Ikbal Rizki Putra; Ida Ristiana; Aulia Puji Rahayu (Universitas PGRI Yogyakarta, 2025)
Sekar Makmur Women Farmers Group (KWT) in Trimulyo Village, Jetis Sub-district, Bantul Regency is a productive community focusing on processing agricultural products such as cassava chips, bio-char briquettes, and organic compost. Nevertheless, their production capacity and product value remain limited due to several constraints: traditional cassava slicing, frying that relies on firewood and gas, a relatively long composting process, and unutilized rice-husk waste. This community service program aimed to enhance production efficiency and capacity through the application of appropriate technology (TTG) while strengthening managerial skills and digital marketing strategies to broaden market reach. The program was carried out in five stages: socialization, training, technology implementation, technology utilization assistance, and sustainability planning. Results show significant improvements in production, management, and marketing aspects. The TTG application increased empowerment levels: cassava slicing machine by 19.15%, rice-husk bio-char briquettes by 100%, and compost mixer by 12%. These outcomes demonstrate that appropriate technology combined with improved managerial capacity and digital marketing effectively raises product competitiveness, promotes sustainable agriculture, and empowers rural women, providing a replicable model of community empowerment. Keywords: empowerment improvement; Sekar Makmur Women Farmers Group; cassava slicer TTG; rice husk bio-char; compost mixer.